Pengaruh Penambahan Ampas Teh terhadap Sifat Fisis Tanah Lempung melalui Uji Laboratorium - Muhammad Adam Nugraha; Athaya Zhafirah (Jurnal Konstruksi, 2026)
Tea waste is generally discarded and has not been optimally utilized, even though tea is one of the most popular beverages in Indonesia. In many cases, tea waste in the form of spent leaves and residual liquid is simply thrown away. One potential use of tea waste is as a soil additive for stabilization purposes. This study investigates the mixing of clay soil with tea waste. Chemical analysis under dry conditions indicates that tea waste contains polyphenolic compounds such as catechins and theaflavins, which possess antioxidant properties and can function as binding agents in composite construction materials. This research aims to examine the physical properties of clay soil with the addition of tea waste at proportions of 5%, 10%, and 15%. The study was conducted at the Civil Engineering Laboratory of the Institut Teknologi Garut, using clay soil obtained from Cintakarya Village, Garut Regency. The tea waste was collected from Sederhana Jaya 2 Restaurant. The methodology involved laboratory testing of soil physical properties, including water content, sieve analysis, liquid limit, shrinkage limit, plastic limit, specific gravity, and bulk density. The results show that the addition of tea waste affects the physical properties of clay soil, causing both decreases and increases in several parameters, with the most significant changes observed at the 15% proportion. Decreases were observed in water content (26.62%), fine particle fraction (36.03%), liquid limit (22.04%), shrinkage limit (12.49%), and plasticity index (30.97%). In contrast, increases occurred in bulk density (0.4 g), specific gravity (0.66 g), plastic limit (8.93%), and coarse particle fraction (36.83%).